The Illustrated Storybooks Advancement as the Literacy Movement for Preparing the Minimum Competency Assessment in Elementary School - Rizky Arianty; Ani Rusilowati; Mukh Doyin (JTP - Jurnal Teknologi Pendidikan, 2021)
The National Assessment policy, well-known as Asesmen Nasional (AN), as the replacement for the National Examination, had been implemented. The Minimum Competency Assessment or Asesmen Kompetensi Minimum (AKM) is a part of AN, which examines the reading, numeracy literacies and the cultivation of good character for the students. During the COVID-19 pandemic, the implementation of AKM faces challenges for every educational system in improving the literacy rate among the students. Therefore, learning media is highly required which following the needs and the characteristics of students as well as the environmental condition so that it can be used for either online or offline learning. The research purpose is to develop a digital product of illustrated storybooks to prepare the students in facing the AKM. The research and development process is according to the ADDIE model, with a quasi-experimental trial design. The digital illustrated storybooks are designed based on the competency achievement of AKM, particularly the reading and numeracy literacies. The research result shows that the product of the illustrated storybooks demonstrates the criteria according to the needs, characteristics and environmental conditions. The digital illustrated storybooks are also considered suitable for the students, lead the students easily understand the content, attractive and effectively used in the learning process for the First Grade of elementary school students. Furthermore, the digital illustrated storybooks are proven to help the students in improving the reading and numeracy literacies in accordance with the achievements in the AKM.